Толковый словарь по искусственному интеллекту - Аверкин Алексей Николаевич (Радио и связь, 1992)
Экземпляры: КХ (20081022) / Инвентарный номер: 1000647 / Цена: 40.00 / Сис.шифр: 32.81 / Авт.знак: Т 52 / ГРНТИ: 20 / ББК: 32.813